The impact of the internal welding defects on the joint strength - Didžiokas, Rimantas; Janutėnienė, Jolanta; Jonaitytė, Jurgita (Transport, 2008)
The paper looks at the impact of the internal welding defects on the strength of joints. The tension tests provided the values of the welded joint strength limits depending on the area of sporadic voids, slag intrusions and the field of discontinuities. Considering the results of the conducted experiments, the mathematical relationships between the strength of the welded joint and defected area were concluded. In presence of all three defects, the distance of the defects from the weld surface was measured. It is deduced that the defects nearer to the surface reduce the strength of the welded joint more than those noticed in deeper layers. First published online: 27 Oct 2010